The missionary journey of Mark 6 and the experience of ministry in today"s world: An empirical study in biblical hermeneutics among Anglican clergy - Francis, Leslie J. (HTS teologiese studies, 2017)
This study explores the connection between dominant psychological type preferences and reader interpretations of biblical texts. Working in type-alike groups (dominant sensing, dominant intuition, dominant feeling and dominant thinking), a group of 40 Anglican clergy (20 curates and 20 training incumbents) were invited to employ their strongest function to engage conversation between Mark’s account of Jesus sending out the disciples (Mk 6: 6b–16) and the experience of ministry in today’s world. The data supported the hermeneutical theory proposed by the SIFT approach to biblical interpretation and liturgical preaching by demonstrating the four clear and distinctive voices of sensing, intuition, feeling and thinking.